Pengaruh Brand Hate Terhadap Negative Word Of Mouth, Continued Intentions To Use, dan Brand Equity Pada Pelanggan Mcdonald’s di Indonesia Selaku Brand Pro Israel - Anisa, Mu'arifia; Suryani, Tatik (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
This research aims to analyze and identify the influence of brand hate on negative word of mouth, continued intentions to use, and brand equity among McDonald's customers in Indonesia as a pro-Israel brand. Research was conducted on consumers or customers who had made purchases at McDonald's in the last few months with a total population of 105 people. The sample used was only 100 respondents because some samples did not match the criteria. The data collection technique used was a questionnaire via Google Form. Variable measurement uses a Likert scale with a scale of 1-7 and analysis for data processing uses the SEM-PLS method with the Smart-PLS application ver. 3.0. The results of the research show that there is an influence of brand hate on negative word of mouth, continued intentions to use, and brand equity on McDonald's customers in Indonesia as a pro-Israel brand.